PENGARUH SOLUTION FOCUSED BRIEF COUNSELLING (SFBC) DALAM MENCEGAH BURNOUT SYNDROME PADA MAHASISWA KEPERAWATAN SEMESTER AKHIR - Sugesti Aliftitah (Fakultas Ilmu Kesehatan, 2016)
Introduction: Stress cause nursing students change of behaviour e.g derivation of interest and activity, absent or late, Inclined to express cynicism to another, anger, shyness, dissappointed, frustrated, confused, pesimistic and weakening of responsibility. The early study of 12 nursing students in health faculty of wiraraja university, didn’t have enthusiasm in class 58,3% , anxiety 33,3 %, physically derangement (feeling sick, headache. etc) 42%, sleep disturbance or insomnia 67%. If the stress condition couldn’t get over with or advanced, it can be directed to burnout. This study aims to explain the effect of Solution Focused Brief Counselling (SFBC) to prevent burnout syndrome of nursing students in the final semester.Method: This is a quasi-experimental study with pretest - posttest control group design. Sample amount was 40 enrolled by means of simple random sampling technique. Sample was divided into two groups: treatment and control groups. Independent variable was Solution Focused Brief Counselling (SFBC) while dependent variables were burnout syndrome. Instruments used were MBI-SS with 16 question. Data analysis was using descriptive statistic, Paired t-test, Independent T-Test; α<0.05.Result and Discussion: Paired T test showed that treatment group before and after intervention was significant (p < 0,05). It means there was significant differences before and after intervention in treatment group. The control group before and after got motivation from academic adviser was significant (p < 0,05). It means there was significant differences before and after intervention in control group. The paired t test of each burnout dimension were significant except in professional efficacy dimension in treatment group. The result of this study suggests that Teachers, may enable to motivate and counsel the student with high risk of burnout. It will be advantageous, if teachers have capability to give counselling especially SFBC technic by participating in counselling workshop.